Cause and level of treatment of injuries from earthquake damage to commercial buildings in New Zealand. Issue 3 (August 2020) - Yeow, Trevor; Baird, Andrew; Ferner, Helen; Ardagh, Michael; Deely, Joanne; Johnston, David
This study assesses the number of injuries directly caused by structural and non-structural damage within New Zealand commercial buildings from notable shaking events between 2010 and 2014 and the treatment level required. After applying filtering to a comprehensive New Zealand earthquake-induced injury database, 947 injuries matched this study's scope, of which 174 were fatal. Collapse or movement of non-structural elements caused 556 injuries; though over 85% were treated outside hospitals and none were fatal. In contrast, 60% of the 220 structural damage-related injuries were fatal. The high injury occurrence from non-structural damage highlights its high risk of injury burden. The two leading causes of non-structural damage-related injuries were movement and/or damage of contents (e.g. furniture) and ceiling and services damage. This emphasizes the importance of reducing injury from movement and damage of non-structural elements during earthquake shaking, in addition to reducing fatalities by preventing structural and masonry collapse.